Neutrophils pro‐inflammatory and anti‐inflammatory cytokine release in patients with heart failure and reduced ejection fraction. (12th August 2021) - Chaar, Diana; Dumont, Benjamin; Vulesevic, Branka; Neagoe, Paul‐Eduard; Rakel, Agnes; Sirois, Martin G.; White, Michel
Abstract: Aims: Heart failure with reduced ejection fraction (HFrEF) is characterized by sub‐clinical inflammation. Changes in selected biomarkers of inflammation concomitant with the release of pro‐inflammatory and anti‐inflammatory cytokines by neutrophils have not been investigated in patients with HFrEF. Methods and results: Fifty‐two patients, aged 68.8 ± 1.7 years, with HFrEF and left ventricular ejection fraction 28.7 ± 1.0%, and 21 healthy controls (CTL) were recruited. Twenty‐five HF patients had type 2 diabetes. Venous blood samples from HF and CTL were collected once. Neutrophil‐derived pro‐inflammatory and anti‐inflammatory cytokine levels were assessed in plasma by ELISA. Plasma biomarkers assessed included: C‐reactive protein (CRP), vascular endothelial growth factor (VEGF), interleukins (IL)‐6, ‐8, ‐1 receptor antagonist (‐1RA), nitric oxide (NO), soluble intercellular adhesion molecule‐1 (sICAM‐1), vascular cell adhesion molecule 1 (sVCAM‐1) and E‐Selectin (sE‐Sel). Neutrophils were isolated and stimulated with various agonists to promote VEGF, IL‐6, IL‐8, and IL‐1RA release. Compared with CTL, HFrEF patients showed a marked decrease in circulating VEGF [178.0 (interquartile range; IQR 99.6; 239.2) vs. 16.2 (IQR 9.3; 20.2) pg/mL, P ≤ 0.001] and NO [45.2 (IQR 42.1; 57.6) vs. 40.6 (IQR 30.4; 47.1) pg/mL, P = 0.0234]. All other circulating biomarkers were significantly elevated. Neutrophils isolated from patients with HFrEF exhibited a greater IL‐8 release in response to LPS [1.2 ± 0.1 (CTL); 10.4 ± 1.6 ng/mL (HFrEF) and 12.4 ± 1.6 ng/mL (HFrEF and DM), P ≤ 0.001]. IL‐6 release in response to LPS was not changed in HFrEF patients without diabetes, whereas it was significantly increased in patients with HFrEF and diabetes [46.7 ± 3.9 (CTL) vs. 165.8 ± 48.0 pg/mL (HFrEF), P = 0.1713 and vs. 397.7 ± 67.4 pg/mL (HFrEF and DM), P ≤ 0.001]. In contrast, the release of VEGF and IL‐1RA was significantly reduced in HFrEF (VEGF; TNF‐α: 38.6 ± 3.1 and LPS: 25.3 ± 2.6 pg/mL; IL1RA; TNF‐α: 0.6 ± 0.04 and LPS: 0.3 ± 0.02 ng/mL) compared with CTL (VEGF; TNF‐α: 60.0 ± 9.4 and LPS: 41.2 ± 5.9 pg/mL; IL1RA; TNF‐α: 3.3 ± 0.2 and LPS: 2.3 ± 0.1 ng/mL). Conclusions: Patients with HFrEF exhibit a significant decrease in circulating VEGF. The release of VEGF and both pro‐inflammatory and anti‐inflammatory cytokines from the stimulated neutrophils is markedly altered in these patients. The clinical significance of these findings deserves further investigation.